Cost-effectiveness of bilateral versus single internal thoracic artery grafts at ten years - Little, M; Gray, A; Altman, DG; Benedetto, U; Flather, M; Gerry, S; Lees, B; Murphy, J; Gaudino, M; Taggart, D (Oxford University Press, 2021)
Objectives: Using bilateral internal thoracic arteries (BITA) for coronary artery bypass grafting (CABG) has been suggested to improve survival compared to CABG using single internal thoracic arteries (SITA) for patients with advanced coronary artery disease. We used data from the Arterial Revascularisation Trial (ART) to assess long-term cost-effectiveness of BITA grafting compared to SITA grafting from an English health system perspective.